Aos jovens compatriotas do Brasil independente: os resumos de História do Brasil de 1831 e 1834 de Henrique L. N. Bellegarde - João Pedro Menezes Jacinto (2020)
Through the analysis of the content of two versions of the Summary of Brazilian History, by Henrique Luiz de Niemeyer Bellegarde, published in 1831 and 1834, this dissertation aimed to understand some contents, concepts and perspectives present in these pieces of work, and to compare them in their differences and similarities to the work of the French traveler Jean Ferdinand Denis. The French version, which served as an “inspiration” for Bellegarde, was published in 1825. In order to perform the proposed comparison between the three editions, the thematic outline was defined: 1) the so-called “first seasons” and Brazil before conquest; 2) from Palmares to the blacks of Palmares; 3) the trip of the Portuguese royal family; 4) the Independence and the awakening of the Empire. The interest in publications in Portuguese comes from the fact that they were intended for young compatriots, and it is important to highlight their authorization for use as a textbook at Imperial School Pedro II, starting in 1841. Among the aspects taken into consideration for the execution of the analysis, it was necessary to present the changes in the educational legislation and the context of the educational initiatives of the time in which they were produced, presenting the amendment of the school training itineraries, the family relationships and the groups belonging to the authors of the publications, and the concepts used in the dialogue with the sources were intelectual concepts and textbooks. It was concluded that, although initially “warned” that the publication was a translation, and later “warned” that it was a totally new edition, none of the warnings of the PortugueseBrazilian author is consistent with the reality of the pieces of work analyzed.